(untitled) (Perner’s Contacts, 2006)
In the presented article the authors follow selected problems of brake fluids evaluation. The introductory section briefly specifies their application. Next section refers to the degradation effects of practical operation and to the methods and instruments for the evaluation of the selected quality properties of brake fluids.